2022
DOI: 10.19080/jhnss.2022.04.555646
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Approach for Markerless Head-Neck Posture Assessment

Abstract: With the increasing digitization at work and in the private sphere, the use of digital devices also on the rise. Particularly when using smart devices, the user unconsciously adopts a posture that deviates from a low-strain posture. The problem here is that daily use, in some cases over long periods of time, can lead to symptoms of overuse. In this study, the postural assessment of the upper-body is performed, and functional relationships between different postures are analyzed. To that end, the Craniovertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…NF typically encompasses the forward flexion of both the head and the cervical spine as a unified unit, while HF refers to head bending with the upper cervical spine acting as the axis of rotation. Indeed, the mechanism of forward head and neck flexion varies fundamentally with posture [9]. Research also demonstrated that two-handed texting engendered larger NF compared to one-handed browsing, and this divergence is primarily attributed to distinct visual demands among tasks [3,4,10].…”
Section: Introductionmentioning
confidence: 99%
“…NF typically encompasses the forward flexion of both the head and the cervical spine as a unified unit, while HF refers to head bending with the upper cervical spine acting as the axis of rotation. Indeed, the mechanism of forward head and neck flexion varies fundamentally with posture [9]. Research also demonstrated that two-handed texting engendered larger NF compared to one-handed browsing, and this divergence is primarily attributed to distinct visual demands among tasks [3,4,10].…”
Section: Introductionmentioning
confidence: 99%